A constituição originária do mecanismo de rejeição (Verwerfung) pela perspectiva de Wilfred Ruprecht Bion e Jacques Lacan - Fonseca, Rodrigo Otávio (2014)
Psicose was always, for Freud, a fenomenom which symptoms were certainly proportional to the radicalism of the defense mechanisms which are busy with it. Among the possibilities of searching a metapsycological unterstanding, Freud thinks about a more primitive and radical mechanism than the repression, which could work decisively to cause psychosis. Considering an hallucinatory incident that was lived by Ergei Pankejeff, The Wolves Man, Freud calls this mechanism as rejection (Verwerfung). Without a systematic continuity of the research on psychosis, new heirs to the Master developed new ideas not only about psychosis but also about its psycological operation. That s what happened to the psychiatries Wilfred R. Bion and Jacques Lacan. Even if they are from different schools of thought and have different traditions, both consider the diversity of the psychotic categories (Bion with schizophrenia and Lacan with paranoia) to develop their systems of the psychoanalytic thought abou the theme. The originality and the diversity of their ideas make the authors have particular view points about the psychic mechanisms of psychosis; by the way, even withou a dialogue between them, some of their propositions can be considered very similar. The objective of this study is to consider mainly the concept of the defense mechanism called rejection (Verwerfung) e its connections between Wilfred Bion s and Jacques Lacan s thoughts abou their role on the constitution of the psychic system